Production of Ethanol from Sudanese Sugar Cane Molasses andEvaluation of Its Quality - A. Gasmalla, Mohammed Abdalbasit; Yang, Ruijin , State Key Laboratory of Food Science and Technology, School of Food Science and Technology, Jiangnan University, Wuxi 214122, China; Nikoo, Mehdi; Man, Su (Journal of food processing & technology, 2012)
The objective of the present study was to produce ethanol from final sugar cane molasses and to evaluate its quality. Urea was used as nitrogen source and added at different concentrations 0.15%, 0.5%, and 0.25% (w/v) to the molasses mash. Experiments were conducted using four treatments depending upon molasses sugar concentration which was calculated as percentages 10, 15, 20 and 25(w/v). The pH of the mash was adjusted to 4.8 using concentrated sulphuric acid. 5% (w/v) baker’s yeast was added. The fermentation was conducted for 72 hours at 33°C. The microbiological analysis revealed absence of bacteria, yeasts and moulds in dilutions 10-3, 10-4, 10-5 of molasses samples. The yield of ethanol obtained was 20 ml per 100 g of molasses, and ethanol with 96% purity could be obtained when the main medium of production (molasses) includes 0.25% (w/v) urea and 20% (w/v) sugar concentration.